Por que ser professor?: uma análise da carreira docente na educação básica no Brasil - Alexandre William Barbosa Duarte (2013)
Currently, in Brazil we live with the frequent "denounce" of an imminent collapse of basic education in the country derived from the accentuated drop of the number of teachers in certain stages of educational system and/or areas of knowledge and the consequent increase of the number of enrolments originated from policies of expansion of education carried out in recent decades. Low wages, dissatisfaction with the work and the low professional status are driving away teachers of the public basic education system from this career, and they are now seeking alternatives outside this profession (such as the private sector or teaching in higher education). This is also making young people at the beginning of their careers not to be interested in the teaching profession. Based on this framework commonly exposed in the media of the country, this dissertation aims to understand, in the light of the analysis of public policies of the States of Minas Gerais and Pernambuco, the problem of the low attractiveness of the teaching profession in the Brazilian educational scenario. We observed that, from the evidence of the problem of low attractiveness that has shown the public teaching profession in the country, highlighted by academic institutions, international organizations, trade unions and even by the business sector, the State, in their different scopes, has been creating policies that have as objective the enhancement of the teaching profession and, consequently, to increase its ability to attract new professionals and to maintain the current teachers in this career. For the proposed research were identified and analyzed public policies at national and state level and actions of different sectors of civil society that have focused on the enhancement of the teaching profession and aim the insertion of professionals in this career. From legislative texts of different government bodies and official documents provided by academic institutions, international organizations, trade union and private organizations, we identified that the problem of low attractiveness of the teaching profession has been widely debated in Brazilian educational scenario and generate an intense concern in these various sectors. However, as is emphasized by the representative institutions of the teachers, such policies do not meet the expected results and, often, are acting against the proposed goals, contributing to a strong process of deprofessionalization.